1997
DOI: 10.1103/physrevlett.78.38
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Field-Enhanced Optical Kerr Effect in Absorbing Liquids

Abstract: A large enhancement of the optical Kerr nonlinearity associated with light-induced molecular orientation is observed in a liquid of anisotropic organic molecules when it is doped with a small amount of dye. The effect is ascribed to a photoinduced intermolecular force field, whose orienting action adds to the direct optical field action. The experimental results are in agreement with a model based on such interpretation. The proposed mechanism is in principle very general, and should work in all absorbing liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 5 publications
1
28
0
Order By: Relevance
“…The dyes that cause the effect are known not to undergo photoinduced conformational changes, as in the case with the azo dyes [16]. The enhanced optical reorientation due to dye-doping was also found to be not limited to the liquid crystalline phase, but also present in isotropic liquids, seemingly with the same mechanism at work [17,18,19]. Thus the effect is quite general.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…The dyes that cause the effect are known not to undergo photoinduced conformational changes, as in the case with the azo dyes [16]. The enhanced optical reorientation due to dye-doping was also found to be not limited to the liquid crystalline phase, but also present in isotropic liquids, seemingly with the same mechanism at work [17,18,19]. Thus the effect is quite general.…”
Section: Introductionmentioning
confidence: 57%
“…The same physical underpinnings of the model apply to dye-doped LC in the nematic phase [17,18,19]. It has been suggested that a change in rotational diffusion upon photo-excitation, as observed in our study, could also be the driving force in the optical reorientation of azo-dye systems, working either in conjunction with or, in certain cases, instead of the well-known photo-isomerization of the azo dyes [63].…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…(iv) A dye-induced enhancement of similar magnitude has been observed also in the isotropic liquid phase, where the orientational nonlinearity is a standard optical Kerr one [19,20,21].…”
Section: Jánossy Effect and Related Phenomenamentioning
confidence: 69%
“…This enhancement is sometimes called ''J a anossy effect'', from the name of its discoverer. This effect is actually not even limited to the liquid crystalline phase, as closely related phenomena have been observed also in dye-doped isotropic liquids [2,3].…”
Section: Introductionmentioning
confidence: 79%